A Cobalt‐Free Multi‐Phase Nanocomposite as Near‐Ideal Cathode of Intermediate‐Temperature Solid Oxide Fuel Cells Developed by Smart Self‐Assembly. Issue 8 (15th January 2020) - Song, Yufei; Chen, Yubo; Xu, Meigui; Wang, Wei; Zhang, Yuan; Yang, Guangming; Ran, Ran; Zhou, Wei; Shao, Zongping
Abstract: An ideal solid oxide fuel cell (SOFC) cathode should meet multiple requirements, i.e., high activity for oxygen reduction reaction (ORR), good conductivity, favorable stability, and sound thermo‐mechanical/chemical compatibility with electrolyte, while it is very challenging to achieve all these requirements based on a single‐phase material. Herein, a cost‐effective multi‐phase nanocomposite, facilely synthesized through smart self‐assembly at high temperature, is developed as a near‐ideal cathode of intermediate‐temperature SOFCs, showing high ORR activity (an area‐specific resistance of ≈0.028 Ω cm 2 and a power output of 1208 mW cm −2 at 650 °C), affordable conductivity (21.5 S cm −1 at 650 °C), favorable stability (560 h operation in single cell), excellent chemical compatibility with Sm0.2 Ce0.8 O1.9 electrolyte, and reduced thermal expansion coefficient (≈16.8 × 10 −6 K −1 ). Such a nanocomposite (Sr0.9 Ce0.1 Fe0.8 Ni0.2 O3– δ ) is composed of a single perovskite main phase (77.2 wt%), a Ruddlesden–Popper (RP) second phase (13.3 wt%), and surface‐decorated NiO (5.8 wt%) and CeO2 (3.7 wt%) minor phases. The RP phase promotes the oxygen bulk diffusion while NiO and CeO2 nanoparticles facilitate the oxygen surface process and O 2− migration from the surface to the main phase, respectively. The strong interaction between four phases in nanodomain creates a synergistic effect, leading to the superior ORR activity. Abstract : A cobalt‐free multi‐phase nanocomposite with a superior electrochemical activity for oxygen reduction is developed as a near‐ideal cathode of intermediate‐temperature solid oxide fuel cells (SOFCs) via a smart self‐assembly strategy. Sr0.9 Ce0.1 Fe0.8 Ni0.2 O3– δ is a highly promising cathode material for SOFCs, suitable for the efficient and stable operation at the intermediate‐temperature range.